Multiple bee stings, multiple organs involved: a case report - Luana Ferreira Martins de Toledo; Daniella Campelo Batalha Cox Moore; Daniella Mancino da Luz Caixeta; Margarida dos Santos Salú; Carla Verona Barreto Farias; Zina Maria Almeida de Azevedo (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract Accidents related to Africanized honey bees are growing globally and are associated with multiple stings owing to the aggressive behavior of this species. The massive inoculation of venom causes skin necrosis and rhabdomyolysis leading to renal failure. Anaphylactic manifestations are more common and are treated using well-defined treatment protocols. However, bee venom-induced toxic reactions may be serious and require a different approach. We report the case of a 3-year-old child, which would help clinicians to focus on the treatment approach required after an incident involving multiple bee stings.